2015
DOI: 10.1016/j.bbmt.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Total Nucleated and CD34+ Cell Dose on Outcome after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: During more recent years only few studies have analyzed the effect of total nucleated cell (TNC) and CD34(+) cell dose in allogeneic hematopoietic stem cell transplantation (HSCT). A single-center analysis included 544 patients, 227 with a sibling donor and 317 with an unrelated donor. Most patients (n = 292) were treated with myeloablative conditioning, whereas the remaining patients (n = 252) received reduced-intensity conditioning. Bone marrow (BM) (n = 121) and peripheral blood stem cell (PBSC) grafts (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 45 publications
(59 reference statements)
10
86
2
Order By: Relevance
“…In the allogeneic setting 2.5-11.0x10 6 CD34 + cells/kg/BW are considered safe. 20 The median number of transplanted cells in our study was 5.81 (MF) and 5.98 (AML)x10 6 CD34 + cells per kg/BW, respectively, and did not correlate with the neutrophil engraftment.…”
contrasting
confidence: 50%
“…In the allogeneic setting 2.5-11.0x10 6 CD34 + cells/kg/BW are considered safe. 20 The median number of transplanted cells in our study was 5.81 (MF) and 5.98 (AML)x10 6 CD34 + cells per kg/BW, respectively, and did not correlate with the neutrophil engraftment.…”
contrasting
confidence: 50%
“…It has been suggested that CD34 cell dose is an important predictor of secondary GF. 13,14 In our study, the lowest total nucleated cell dose infused was 4.3 × 10 8 /kg, and the lowest CD34 dose was 5.29 × 10 6 /kg, which were apparently adequate. Data for our study patients are shown in Table 2.…”
Section: Discussionmentioning
confidence: 46%
“…A total body irradiation-cyclo phosphamide regimen, posttransplant tacrolimus-based immunosuppression, and a granulocyte colonystimulating factor prescription reduce the risk of PGF. 13,14,17 Donor-recipient HLA incompatibility is the prime cause of GF. The GF risk increases as the mismatch HLA allele count increases and when anti- Abbreviations: BM, bone marrow; PB, peripheral blood; TNC, total nucleated cell HLA antibodies are evident in patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…This would include a number of tolerances – the amount of change the product can undergo and still remain functional to the predetermined specification. The current tolerances for cellular therapies, such as blood‐based haematopoietic stem cells, are based on a minimum and optimal threshold criteria; for example, in autologous HSCT derived from peripheral blood, the minimum is considered to be 2 × 10 6  cells/kg bodyweight and the optimum considered to be 5 × 10 6  cells/kg bodyweight 2, 3. Reducing variation decreases the number of defects within the product line, and increases its overall quality at a reduced cost – for cellular therapy, this would mean maximizing patient longevity and quality of life while minimizing costs.…”
Section: Contextmentioning
confidence: 99%